Analisis Pembiayaan Murabahah dan Solusi Permasalahannya pada BMT Rizky Barokah Cabang Talun Magelang - Yulita, Siska; Panggiarti, Endang Kartini (Jurnal Maps (Manajemen Perbankan Syariah), 2020)
The murabahah finance is sell and buy transaction which is seller acknowledge selling price and buyer pay to the seller as much as the price plus margin that being approved. Sometimes on going murabahah finance promise found obstacles and resistance being faced bank or debtor party. There for, we want to study more deep about murabahah finance in BMT RIzky Barokah as a research object. The research aims to analysis of the operation of murabahah finance, analysis of murabahah operation in KSPPS BMT Rizky Barokah with Fatwa Dewan Syariah Nasional (DSN MUI), and analysis of member perception of KSPPS BMT Rizky Barokah about murabahah finance. This type of research is qualitative research with data analysis techniques, namely data reduction, data display, and conclusion drawing and verification. The result is found conclusion that is process of operationalization of murabahah finance in KSPPS BMT Rizky Barokah different based on object of goods in the murabahah promise. There is a goods that have facilitated by BMT is motor-bicycle but there is have another goods that proxies by another party for the procuration. The execution of murabahah finance promise in Rizky Barokah has appropriate to the commandment and requirement of murabahah and appropriate with fatwa provisions DSN-MUI No. 04/DSN-MUI/IV/2000 about murabahah finance.